UPAYA PENANGGULANGAN TINDAK PIDANA PELECEHAN SEKSUAL ANAK DI MEDIA SOSIAL (Studi di Kepolisian Daerah Polda Metro Jaya) - Khalissa Aliya Indriany (Balitbangda Provinsi Lampung, 2023)
Abstract: When kids have easy access to the internet, it can have both positive and negative consequences. One of the negative influences of recent technological developments is the rise of child cyber grooming, which is especially prevalent in Indonesia. The purpose of this study is to describe efforts to deal with criminal acts of child sexual abuse on social media in the context of legal protection carried out by the Polda Metro Jaya Regional Police. The research method used is an empirical juridical approach with qualitative descriptive data analysis techniques. The results of this study indicate that the effectiveness of legally mandated forms of protection is appropriate to police action. Legal protection given to legal subjects in the form of legal instruments is carried out in a preventive and repressive manner. Keywords: Countermeasures, Social Media, Child Crime